Industrial Training Report : Agriculture Research Station Kabuloh, Miri / Nur Azlin Majs - Majs, Nur Azlin (Universiti Teknologi MARA Cawangan Sarawak Kampus Mukah, 2014)
lndustrial training is a prerequisite to the award of Diploma student’s ln Planting Industry Management, University Teknologi MARA. It is also designed to give exposure and experience to the students about the real situation in their respective fields and early preparation for students before they enter the working world. For sessions from May to October 2013, the training runs for 3 months starting g June until l34September 2014. I was stationed at Stesen Penyelidikan Pertanian Kabuloh, Miri.